2021
DOI: 10.3390/ijerph18157910
|View full text |Cite
|
Sign up to set email alerts
|

Demographic and Habitual Factors of Periodontal Disease among South Indian Adults

Abstract: The aim of this study was to evaluate the performance of a set of sociodemographic and habits measures on estimating periodontal disease among south Indian adults. This cross-sectional study was carried out among 288 individuals above 18 years old in Tamil Nadu, India. The outcome of the study was periodontal disease, measured by WHO criteria. The covariates were age, ethnicity, smoking and alcohol habit. The assessment of factors predicting periodontal disease was carried out by multiple logistic regression a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 36 publications
2
9
0
Order By: Relevance
“…A recent cross‐sectional study involving 1936 adults in London demonstrated that periodontitis was associated with individual and intersectional social characteristics, especially ethnicity and education 38 . Another cross‐sectional study of Indian adults also identified ethnicity as a risk indicator for periodontitis 39 . While the present study did not examine educational status, the results affirm that periodontitis is significantly associated with both race and ethnicity for adults seeking dental care in rural communities in North Carolina.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…A recent cross‐sectional study involving 1936 adults in London demonstrated that periodontitis was associated with individual and intersectional social characteristics, especially ethnicity and education 38 . Another cross‐sectional study of Indian adults also identified ethnicity as a risk indicator for periodontitis 39 . While the present study did not examine educational status, the results affirm that periodontitis is significantly associated with both race and ethnicity for adults seeking dental care in rural communities in North Carolina.…”
Section: Discussionsupporting
confidence: 56%
“…Several psychosocial factors have been associated with oral hygiene behaviors in patients, including self‐efficacy, intention, social influences, coping planning, and action planning 40 . One systematic review found that race, ethnicity, and sex could affect oral health behaviors 41 ; however, the majority of these studies on oral hygiene behaviors have been limited to children and adolescents 34,39,40 . In contrast, the present study included dentate adults, aged 30 years and older.…”
Section: Discussionmentioning
confidence: 92%
“…The existence of dental caries is widespread around the globe, and, on the other hand, 15% of the adult population considerably experience severe periodontal disease [1]. The Indian population has a significant imbalance in oral health care compared to general health [2,3]. Oral health-related conditions can be prevented with proper and effective home oral hygiene measures [4,5].…”
Section: Background Of the Studymentioning
confidence: 99%
“…Similar findings were reported in several other studies. [42][43][44][45] In the current study, neither knowledge nor attitude of participants showed any effect on periodontal disease. Only oral health behavior had a significant association with periodontal disease of individuals.…”
mentioning
confidence: 94%